Nanotechnology Approach for Exploring the Enhanced Bioactivities and Biochemical Characterization of Freshly Prepared Nigella sativa L. Nanosuspensions and Their Phytochemical Profile - Ali, Tayyab; Hussain, Fatma; Naeem, Muhammad; Khan, Ajmal; Al-Harrasi, Ahmed (Frontiers in Bioengineering and Biotechnology, 2022)
Nigella sativa is one of the most commonly used medicinal plants as it exhibits several pharmacological activities such as antioxidant, antibacterial, anticancer, antidiabetic, and hemolytic. The purpose of this study was to apply the nanotechnology approach for exploring the enhanced bioactivities of freshly prepared Nigella sativa L. nanosuspensions and the phytochemical profile of N. sativa seed ethanolic extract. In this study, we performed the biochemical characterization of Nigella sativa L. ethanolic extract through High-performance liquid chromatography (HPLC), Fourier-transform infrared spectroscopy (FT-IR), and Gas chromatography (GC), and bioactivities in terms of antioxidant, antidiabetic, antibacterial, and hemolytic activities of nanosuspension and extract were competitively studied. The results revealed that the nanosuspension of N. sativa seeds showed higher total phenolic (478.63 ± 5.00 mg GAE/100 g) and total flavonoid contents (192.23 ± 1.390 mg CE/100 g) than the ethanolic seed extract. The antioxidant activity was performed using the DPPH scavenging assay, and nanosuspension showed higher potential (16.74 ± 1.88%) than the extract. The antidiabetic activity was performed using antiglycation and α-amylase inhibition assays, nanosuspension showed higher antidiabetic potential [antiglycation (58 ± 0.912%)] and [bacterial α-amylase inhibition (18.0 ± 1.3675%)], respectively. Nanosuspension showed higher biofilm inhibition activity against Escherichia coli (66.44 ± 3.529%) than the extract (44.96 ± 2.238%) and ciprofloxacin (59.39 ± 3.013%). Hemolytic activity was performed and nanosuspension showed higher hemolytic activity than the extract as 7.8 ± 0.1% and 6.5 ± 0.3%, respectively. The study showed that nanosuspension had enhanced the bioavailability of bioactive plant compounds as compared to the ethanolic extract. Therefore, nanosuspension of N. sativa seed extract showed higher biochemical activities as compared to the ethanolic extract. This nanotechnology approach can be used as a platform for the development of combination protocols for the characterization of liquid state nanosuspensions in an adequate manner and also for therapeutic applications.